Design and preparation of high-surface-area Cu/ZnO/Al2O3 catalysts using a modified co-precipitation method for the water-gas shift reaction - Budiman, Adeline; Ridwan, Muhammad; Kim, Sung Min; Choi, Jae-Wook; Yoon, Chang Won; Ha, Jeong-Myeong; Suh, Dong Jin; Suh, Young-Woong (ELSEVIER, 2013)
Highly dispersed Cu/ZnO/Al2O3 catalysts were prepared by modifying a conventional co-precipitation method. By manipulating the preparation conditions, in this case solvent, precipitating temperature, and pH, a Cu surface area of 45.5 +/- 1.7 m(2)/g was prepared, which was much greater than the surface area of 11.4-31.7 m(2)/g obtained by the conventional co-precipitation method and seemed to be the largest Cu surface area ever reported in the literature. The preparation of catalysts with a high Cu surface area was attributed to the formation of aurichalcite, a complex containing Cu and Zn. The catalysts prepared by the modified co-precipitation method were used for a water-gas shift reaction, exhibiting higher catalytic activity compared to those prepared by the conventional co-precipitation method. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: METHANOL SYNTHESIS; CU-ZN; HYDROGEN; AURICHALCITE; TEMPERATURE; REFINEMENT; OXIDES; CO2